Optimizing anesthesiology education for international students in China: challenges and innovative teaching strategies - Yang, Yaoxin; Leng, Yu; Wu, Weiwei (Frontiers in Education, 2025)
With the accelerated internationalization of medical education in China, education of international students has become a key indicator of overall medical education quality. As a highly integrated discipline, anesthesiology requires teaching models that combine theoretical knowledge with practical training, while addressing the diverse cultural and academic backgrounds of international learners. However, anesthesiology education for international students in China faces distinct challenges related to language barriers, culture adaptation and pedagogical alignment. To enhance the quality of anesthesiology education, it is essential to implement innovative and student-centered teaching strategies tailored to their specific needs. This narrative review summarizes the primary challenges encountered in anesthesiology education for international students in China and proposes innovative, student-centered teaching strategies, including bilingual instruction, hybrid models combining problem-based and case-based learning, simulation-based education, and the application of emerging technologies such as AI-assisted learning. Through the enhancement of clinical exposure and the adoption of interactive methods, medical institutions can achieve greater teaching effectiveness, improve clinical competence, and promote equitable learning experiences, ultimately preparing international students to become competent anesthesiologists capable of meeting global healthcare demands in multicultural medical education settings.